Media Mix Mobilization: Social Mobilization and Yo-Kai Watch. (November 2017) - Steinberg, Marc
Animated television programs have been considered an integral element of the 'media mix' or transmedia in Japan. In multiple contexts, the place of such television shows has been framed as a '30-minute commercial' or 'program length commercial'. This article examines the 2014 anime and media mix Yo-kai Watch as an example of the animation episode as something else: part of a call towards total mobilization. Taking seriously the incendiary remarks by one of Japan's media mix pioneers – Kadokawa Haruki – who claimed that his model for the media mix was taken from Hitler's 'total mobilization' of fashion, sound, and image for a nationalist endgame, this article considers the Yo-kai Watch media mix in light of the concept of total mobilization. Through a close analysis of the objects, games and animation of Yo-Kai Watch, the author suggests that the endgame of this media mix geared towards very young audiences is their total mobilization towards collection-based consumption. This means thinking a 'logistics of consumption' that requires in part an examination of the circulation of objects as well as the function of the anime as an incitement and manual to play.